Nurses' burden caused by sleep disturbances of nursing home residents with dementia: multicenter cross-sectional study - Denise Wilfling; Martin N. Dichter; Diana Trutschel; Sascha Köpke (BMC, 2020)
Abstract Background Sleep disturbances are common in people with dementia. In nursing homes, this is frequently associated with residents' challenging behavior and potentially with nurses' burden. This study examined nurses' burden associated with nursing home residents' sleep disturbances. Methods A multicenter cross-sectional study was conducted. Nurses' burden associated with residents' sleep disturbances was assessed using the Sleep Disorder Inventory (SDI). Additionally, the proportion of nurses' total burden associated with sleep disturbances of residents with dementia was assessed. A linear mixed regression model was used to investigate the association with nurses', residents' and institutional characteristics. Results One hundred eleven nurses from 38 nursing homes were included. 78.4% stated to be regularly confronted with residents' sleep disturbances during nightshifts, causing distress. The mean proportion of nurses' total burden caused by residents' sleep disturbances was 23.1 % (SD 18.1). None of the investigated characteristics were significantly associated with nurses' total burden. Conclusions Nurses report burden associated with sleep disturbances as common problem. There is a need to develop effective interventions for sleep problems and to train nurses how to deal with residents' sleep disturbances.